What promotes longevity? - Agnieszka Kujawska; Jakub Husejko; Weronika Topka; Joanna Androsiuk-Perkowska; Natalia Skierkowska; Małgorzata Gajos; Radosław Perkowski; Anna Karpińska; Kamila Kromrych; Marta Kotarska; Natalia Zielińska; Marcin Kożuchowski; et al. (Kazimierz Wielki University, 2017)
Introduction Scientists try to answer on the need of a long life with a full physical capability Nonagenarians, centenarians and their closest family members are characterized by a survival benefit throughout life. Moreover, twin studies of longevity suggest that around 25% of the variation in lifespan in developed countries may be inherited. It is therefore worth to examine the role of inter-relationship between nature vs nurture in longevity increment. Material and methods Articles in the EBSCO database have been analyzed using keywords: longevity, gene, behavior, environment. The available literature was subjectively selected. Then, the newest version of every paper was searched for. Results Restriction of calories as well as intake of desirable nutrients can promote adequate control of metabolic pathways and gene expression. APOE, DRD4, Paraoxonase 1, SIRT 3 and SIRT 5 genes can play an important role in longevity. Conclusions Genetic profile and environmental factors seems to both influence on the longevity. Relationships between genetic profile, behavior pattern, quality of life, years spent free from activity limitations and longevity should be examined, to be able to give a recipe on living a long and happy life.